(untitled) (Acta Polytechnica CTU Proceedings, 2021)
The development of foreign trade plays an important role in the Czech economy. The important foreign trade commodity item is Machinery and transport equipment (SITC 7). Railway vehicles is a part of this category, other means of transport (SITC 79). In order to maintain competitiveness and economic growth, it is necessary for the railway industry to intensify the innovation and the introducing of new technologies into production. One of the available options is a wider implementation of life cycle cost analysis, which enables to activate innovative efforts, as well as to improve technical and performance data.